World trade and workers' rights: to link or not to link? - Hensman, Rohini (2000)
Indian and other developing countries' opposition to linking trade and labour standards is not so much anti-imperialist as pro-domestic business. Allowing exploitation of labour anywhere in the world undermines the rights of all workers around the world. It is possible to incorporate labour standards in trade agreements to help workers everywhere. The institutional resources of the ILO, with funds from the WTO, will make implementation possible. - Reproduced
Keywords: Workers; Labour